弹性啮合与摩擦耦合传动理论及实验研究 - 黄平; 陈扬枝; 朱文坚; 王涛; 何军 (Jixie chuandong)
The structure and the priciple of a new type of mechanical transmission are introduced. This kind of mechanical tramsimission mechanism consists of large mount of elastic teeth. The transimission is realized by the emgagement and the fricrion of these elastic teeth. Therefor, it is called elastic engagement and friction coupled transmission. The theoretical and experimental analysis carried in the paper shows that this mechanical transmission is effective.